Goverment Political Communication : Communication Process and Political Communication Problems Through New Media in the Government of General Prayut Chan-Ocha - Sutcharitpan , Peerapong; Thaboonma , Vayupak (Journal of Modern Learning Development, 2023)
This academic paper aims to study the political communication of the government and the problem of political communication through the new media of General Prayut Chan-ocha's government. It was found that 1) the government's communication process was based on the theory of David K. Berlo in the model S M C R (Source) refers to the government of General Prayut Chan-ocha, the Cabinet and members of the House of Representatives for the first and second terms. (Message) means information sent from the government to the people and various sectors. There are social dimensions, political dimensions. The economic dimension (Channel) refers to the channel for sending government news through new media such as Facebook, Twitter, Instagram, TikTok, or even Sending video clips for broadcasting live (Live) or clips via YouTube channels. It also communicates through personal media such as academics, teachers, artists, politicians and the general public. (Receiver) means recipients from the government or the general public, students, academics, government officials, private employees, elderly people, etc. 2) Problems in communication of the government through new media. It was found that there were problems of communication via online media or new media as follows: social media problems may not be politically neutral. Social media problems are formal and less regulated, lack of flexibility. The government's use of social media is limited. Problems of cyber bullying, identity theft, and enforcement of the Computer Crime Act B.E. 2560 (2017).